ETIOLOGICAL STRUCTURE, PROPHYLAXIS, TREATMENT OF POSTOPERATIVE AND POSTTRAUMATIC INFECTIOUS COMPLICATIONS IN EYE MICROSURGERY - Салдан, Ю.Й.; Назарчук, Г.Г.; Назарчук, О.А. (World of Medicine and Biology, 2016)
The review of literature is dedicated to the study of postoperative and posttraumatic infectious complications’ etiological structure. Special attention is paid to the problem of resistance of stains to antibiotics. The probable ways of prophylactic methods’ perfection are described.
Keywords: infectious complications; endophthalmitis; antibiotics; antiseptics